Employee Turnover Analysis at Pt.XYZ - Kurnia Putri, Dewi; ChristianWiradendiWolor; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Human resources play a crucial role in an organization. A business cannot operate effectively without the support of its HR team. For this reason, the management of human resources within a company is essential. This research examines the turnover analysis of employees at a very high percentage. at the XYZ company, it is known that the employee turnover rate. This research seeks to understand the relationship between the elevated levels of staff turnover and the job satisfaction of employees within the organization., inhibiting factors, and strategies to reduce employee turnover. Data was gathered via interviews, observations, and relevant documents from reliable sources that pertain tothe study. The findings from the research indicate that staff turnover at XYZ company is very high with various contributing factors.XYZ company implements excellent programs to reduce employee turnover rate such as providing compensation, facilities, providing work from home job training program to reduce workload. This research provides insight into how to deal with obstacles by analyzing data on what strategies should be implemented by XYZ company to reduce employee turnover.